Occurrence and abundance of the gymnosome pteropod genus Clione in the coastal waters of Mombetsu, southern Okhotsk Sea, from 2004 to 2012 - Takahashi, Kunio T.; Katakura, Seiji; Hamaoka, Soshi; Kuwahara, Takashi; Yamazaki, Tomoyasu (Polar Science, 2022)
Patterns in the seasonal occurrence and abundance of gymnosome pteropods of the genus Clione are described from samples collected during routine monitoring in Mombetsu Harbor, northeastern Hokkaido, Japan, from 2004 to 2012. In this study area of the southern Okhotsk Sea is a unique region where water masses are exchanged seasonally, driven by the East Sakhalin Current (ESC) in winter and the Soya Warm Current (SWC) in summer. Clione elegantissima adults were found between December and early April within a narrow temperature range of −1.79 to 3.78 °C. Most (90.9%) of these individuals occurred in the cold-water mass of the ESC. Veliger and polytrochous larval stages of Clione spp. were observed in all periods, except for late August to early October when the SWC dominated. A positive correlation was found between chlorophyll a concentration and larval abundance using 10-day averaged data. The results indicate that food availability was sufficient to support Clione spp. larval stages in the sampling region. Seasonal exchanges of water mass in the sampling area influence the occurrence of Clione species. journal article